Dichter dran! Neue Möglichkeiten der Vernetzung von Geobasis-, Statistik- und Erdbeobachtungsdaten zur räumlichen Analyse und Visualisierung von Stadtstrukturen mit Dichteoberflächen und -profilen - Fina, Stefan; Krehl, Angelika; Siedentop, Stefan; Taubenböck, Hannes; Wurm, Michael (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
In urban research and planning, “density” is one of the most important measures to analyze a city’s structural morphology. Compared to other measures such as “neighborhood mix of uses”, “polycentricity” or “compactness”, density seems to be a rather objective and comprehensible choice. However, when having a closer look at it, it is a rather complex concept with different measurement options. There is no internationally accepted standard for the implementation of density or density measures that would allow for a robust comparison of different countries, regions or cities. This article deals with the analytical opportunities that new geodata options offer with regards to an objective and transparent measurement of cities’ structural and use-related densities. A case study for the city of Cologne demonstrates possible applications based on high-resolution and disaggregated density data.